Explaining the Evolution of Job Tenure in Europe, 1995–2020 - Bussolo, Maurizio (World Bank, Washington, DC, 2022)
During the last quarter century, job tenure in Europe has shortened. Using data from Eurostat Labor Force Surveys of 29 countries from 1995 to 2020 and applying an age-period-cohort decomposition to analyze changes in tenure for specific birth cohorts, this paper shows that tenure has shrunk for cohorts born in more recent years. To account for compositional changes within cohorts, the analysis estimates the probability of holding jobs of different durations, conditional on individual and employment-related characteristics. The estimations demonstrate that, over time, the likelihood of having a medium- or long-term job decreased and holding a short-term job increased. The paper also finds that stricter job protection legislation appears to decrease the probability of holding a short-term job, and higher trade openness and ICT-related technological change are correlated with an increase of that probability.